2018
DOI: 10.1145/3191743
|View full text |Cite
|
Sign up to set email alerts
|

You Are Sensing, but Are You Biased?

Abstract: Mobile devices are becoming pervasive to our daily lives: they follow us everywhere and we use them for much more than just communication. These devices are also equipped with a myriad of different sensors that have the potential to allow the tracking of human activities, user patterns, location, direction and much more. Following this direction, many movements including sports, quantified self, and mobile health ones are starting to heavily rely on this technology, making it pivotal that the sensors offer hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 35 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The performance of different sensors varies across different types of devices but also between individual devices of the same model (e.g., Chaffin et al, 2017;Kuhlmann et al, 2021;Stisen et al, 2015;Woo et al 2020). Smartphone sensors are often poorly built and calibrated (e.g., Blunck et al, 2013;Grammenos et al, 2018;Stisen et al, 2015) because manufacturers want to reduce costs and because sensors only need to perform sufficiently well for their intended uses which do not include scientific behavioral assessment. Sensor accuracy may also change slowly over time (natural drift; e.g., Kuhlmann et al, 2021) or due to external forces, such as when the device is dropped (Stisen et al, 2015).…”
Section: Device Type Biasmentioning
confidence: 99%
“…The performance of different sensors varies across different types of devices but also between individual devices of the same model (e.g., Chaffin et al, 2017;Kuhlmann et al, 2021;Stisen et al, 2015;Woo et al 2020). Smartphone sensors are often poorly built and calibrated (e.g., Blunck et al, 2013;Grammenos et al, 2018;Stisen et al, 2015) because manufacturers want to reduce costs and because sensors only need to perform sufficiently well for their intended uses which do not include scientific behavioral assessment. Sensor accuracy may also change slowly over time (natural drift; e.g., Kuhlmann et al, 2021) or due to external forces, such as when the device is dropped (Stisen et al, 2015).…”
Section: Device Type Biasmentioning
confidence: 99%
“…A novel multilocation calibration scheme was introduced specifically to target mobile devices, and the scheme exploited machine learning techniques to perform an adaptive, power-efficient auto-calibration procedure through which it achieved a high level of output sensor accuracy when compared to that of state-of-the-art techniques [3]. An on-site sensor calibration method was proposed for the quality assurance of process separation measurements, which can guarantee the optimal performance of the sensor measuring system and assure a high measurement quality between company inspections [4]. More reviews can be found in [5][6][7].…”
Section: Introductionmentioning
confidence: 99%